Pratiques argumentatives et dynamique interactionnelle des échanges en classe de FLE : analyse pragmatique des interactions verbales d'apprenants algériens en situation de débat - Naima Hocine (Nantes Université, 2011)
The skill in oral expression, which represents one in the most important aspects of the acquisition of a foreign language, acquires itself in situations of verbal interaction. The present article has for objective to describe the interactional dynamics which develops in communicative argumentative activities in class of language. This study which concerns conceived debates as activities of learning and which took place in classes of FLE with Algerian learners of first secondary year consists in loosening and in analyzing the communications strategies used by the learners as well as those used by the teacher to bring them to speak. The composed questions, the speaking slots, the attitude of the teacher and the communications strategies in a class establish the essential point's object of our observation